Analisis Kemampuan Merancang Perangkat Pembelajaran Matematika dan Kinerja Peer Teaching Mahasiswa Prodi PGMI - Nadjamuddin, Asriyati; Pomalato, Sarson W. Dj; Hulukati, Evi (Jambura Journal of Mathematics Education, 2025)
PGMI students, as prospective elementary school teachers, are equipped with specific competencies to ensure they can perform their duties effectively. One of the fundamental competencies required is pedagogical competence, which includes the ability to manage learning processes such as designing and implementing instruction, evaluating learning outcomes, and supporting student development to maximize their potential. Microteaching is a method used to train the teaching skills of prospective teachers in a classroom setting. This study aims to examine the ability of PGMI students to design instructional tools and their performance in peer teaching, as well as to analyze the influence of their instructional design ability on peer teaching performance at FITK IAIN Sultan Amai Gorontalo. The data were analyzed using the Spearman-Rho correlation test and robust regression with M-estimation using Tukey’s bisquare weighting. The results indicate that most students demonstrated good ability in both designing instructional tools and performing peer teaching. The correlation analysis revealed a strong and significant positive relationship between the ability to design instructional tools and peer teaching performance. Furthermore, the robust regression analysis confirmed that the ability to design instructional tools significantly influenced peer teaching performance. The model produced an R-squared value of 78.55%, indicating that this variable explains 78.55% of the variance in peer teaching performance, which is considered a fairly strong contribution.